2017
DOI: 10.1080/20013078.2017.1324731
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of membrane vesicles from prokaryotes: a technical and biological comparison reveals heterogeneity

Abstract: Prokaryotes release membrane vesicles (MVs) with direct roles in disease pathogenesis. MVs are heterogeneous when isolated from bacterial cultures so Density Gradient Centrifugation (DGC) is valuable for separation of MV subgroups from contaminating material. Here we report the technical variability and natural biological heterogeneity seen between DGC preparations of MVs for Mycobacterium smegmatis and Escherichia coli and compare these DGC data with size exclusion chromatography (SEC) columns. Crude preparat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(92 citation statements)
references
References 63 publications
2
84
0
1
Order By: Relevance
“…Microvesicles that separated at approximately 10 to 14,000 g are heterogeneous. In contrast, microvesicles separated at 100,000 g are homogeneous [17,[23][24][25]. Apoptotic bodies with large populations originate from membrane blebbing and cellular disassembly from cell fragmentation when the cytoskeleton breaks at the beginning of apoptosis.…”
Section: Classification Of Evsmentioning
confidence: 99%
“…Microvesicles that separated at approximately 10 to 14,000 g are heterogeneous. In contrast, microvesicles separated at 100,000 g are homogeneous [17,[23][24][25]. Apoptotic bodies with large populations originate from membrane blebbing and cellular disassembly from cell fragmentation when the cytoskeleton breaks at the beginning of apoptosis.…”
Section: Classification Of Evsmentioning
confidence: 99%
“… 2014a ; Dauros Singorenko et al. 2017 ). However, given the propensity of lipids to organize into vesicles-like structures, it is important to establish that recovered nanoparticles are not byproducts of cell lysis.…”
Section: Introductionmentioning
confidence: 99%
“…In their native form, OMVs contain high amounts of lipopolysaccharides (LPS) that can elicit immune responses; thus, several studies have been done to modify bacterial strains into detoxified LPS to reduce the endotoxicity of OMVs [30]. In addition, the findings of Dauros Singorenko et al [31] have shown that samples purified using size exclusion chromatography contained lower amounts of LPS when compared to the crude sample. For further verification, cytotoxicity studies of the system developed here are planned for future work.…”
Section: Resultsmentioning
confidence: 99%